1985
DOI: 10.1002/j.1460-2075.1985.tb03878.x
|View full text |Cite
|
Sign up to set email alerts
|

A glia-derived neurite-promoting factor with protease inhibitory activity.

Abstract: Brain cells and glioma cells in culture release a protein which induces neurite outgrowth in neuroblastoma cells. This neurite‐promoting factor (NPF), which has been purified from serum‐free glioma conditioned medium, has an apparent mol. wt. of 43 000. NPF inhibits urokinase as well as plasminogen activator‐dependent caseinolysis or fibrinolysis. NPF and urokinase form an SDS‐resistant complex. The fact that this glia‐derived NPF is a potent protease inhibitor indicates that glial cells modulate the proteolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
184
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(188 citation statements)
references
References 30 publications
4
184
0
Order By: Relevance
“…In several cases, we observed that a fraction of the labelled uPA migrated with an apparent molecular size larger than that of the Mr 33 000 free enzyme (lane 1). In view of the known ability of uPA to form SDS-resistant complexes with different serpin-class antiproteases (Baker et al, 1980;Vassalli et al, 1984) (Baker et al, 1980;Guenther et al, 1985;Stone et al, 1987). Likewise, the uPA ligand in seminal vesicle could be quantitatively adsorbed on heparin -Sepharose, and eluted using a salt gradient at -0.5 M NaCl (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In several cases, we observed that a fraction of the labelled uPA migrated with an apparent molecular size larger than that of the Mr 33 000 free enzyme (lane 1). In view of the known ability of uPA to form SDS-resistant complexes with different serpin-class antiproteases (Baker et al, 1980;Vassalli et al, 1984) (Baker et al, 1980;Guenther et al, 1985;Stone et al, 1987). Likewise, the uPA ligand in seminal vesicle could be quantitatively adsorbed on heparin -Sepharose, and eluted using a salt gradient at -0.5 M NaCl (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…PN-l is secreted by the adult mouse seminal vesicle Cultured human fibroblasts and rat glioma cells release PN-I into the medium (Baker et al, 1980;Guenther et al, 1985). To determine whether PN-I is present in the seminal vesicle secretory product, the amounts of PN-I in an extract of glandular tissue ( Figure 5, lanes 5 and 6) and in the liquid secretion (lanes 7 and 8) were compared with that in an unfractionated extract (lanes 2-4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the coagulation /fibrinolytic pathway where several different inhibitors are known, in the CNS only protease nexin-1 (PN-1; Guenther et al, 1985;Sommer et al, 1987) is present at significant levels (Mansuy et al, 1993;Sappino et al, 1993;Reinhard et al, 1994). PN-1 is expressed in both glial and neuronal cells of the developing and adult CNS (Mansuy et al, 1993;Sappino et al, 1993;Reinhard et al, 1994) and in glomeruli of the olfactory bulbs, where synapse formation and elimination remain an active process throughout life (Reinhard et al, 1988;Mansuy et al, 1993).…”
mentioning
confidence: 99%
“…Both OECs and astrocytes within the NFL of the olfactory bulb also express protease nexin-1 (PN-1; Reinhard et al, 1988;Scotti et al, 1994), whereas astrocytes elsewhere in the CNS do not express this enzyme. PN-1 has been demonstrated to function as a chemotropic factor for neurites in vitro (Monard et al, 1973;Guenther et al, 1985;Zurn et al, 1988) and could potentially be functioning in the same manner within the primary olfactory pathway.…”
Section: Oecs Normally Differentiate Into Nonmyelinating Gliamentioning
confidence: 99%